Anticancer properties and biological evaluation of natural alkaloid jerantinine B - Qazzaz, Mohannad Emad (2017)
Natural products play a pivotal role in medicine especially in the cancer arena. Many drugs that are currently used in cancer chemotherapy originated from or were inspired by nature. The toxicity and growth inhibitory activity of novel extracts of five different species of Malaysian rainforest plants, which are Melodinus species, Daphniphyllum scortechinii, Ficus fistulosa, Kopsia arborea and Tabernaemontana corymbosa, were investigated. The preliminary screening and chemical structure of jerantinine B highlighted this compound to be selected as a focus of this PhD study. Jerantinine B (JB) is one of seven novel Aspidosperma indole alkaloids isolated from the leaf extract of Tabernaemontana corymbosa. JB was previously evaluated to be one of the most potent cytotoxic jerantinine among all jerantinines against vincristine-sensitive and vincristine-resistant human oral epidermoid carcinoma cell lines. Furthermore, structural similarity of JB with the lower half of the vincristine chemical structure is therefore highlighted this compound to be a valuable candidate for biological evaluation. Herein, detailed biological evaluation of JB and its acetate derivative (jerantinine B acetate) on various human-derived carcinoma cell lines are reported. Our preliminary investigation showed significant inhibition of cell growth in sensitive and vincristine-resistant cancer cell lines, accompanied by significant inhibition of cell counts and colony formation associated with induction of apoptosis in human cancer cell lines after exposure to jerantinine B. Significant dose-dependent upregulation of apoptosis biomarkers (cleaved PARP and caspase 3) was shown and further confirmed apoptosis. Inhibition of cancer cell migration and invasion was observed after exposure of cells to JB. Profound G2/M cell cycle arrest was observed after treatment of cancer cell lines with JB. Tubulin polymerisation was significantly inhibited by JB and JB acetate. Morphological characterisations of mitotic arrest and apoptosis including microtubule disruption, multi-nucleation, DNA fragmentation, and membrane blebbing were obviously demonstrated by confocal microscopy in JB-treated cells. Indeed, significant interference in the dynamicity of microtubules caused by JB was observed and was relatively similar to that caused by vincristine and colchicine. Binding affinity of JB to heterodimeric tubulin protein was confirmed, measured and compared to vincristine and colchicine. Both JB and colchicine were shown to exhibit a cooperative binding response compared to vincristine which was characterised by no cooperative interaction with tubulin protein. The high-resolution crystal structure was obtained finally showing that JB acetate binds to the colchicine site on microtubules. Polo-like kinase 1 (PLK-1; an early trigger for the G2/M transition) was also dose-dependently inhibited by JB. Investigating a secondary mechanism by which jerantinine induces apoptosis, inhibits microtubule assembly and overcomes vincristine resistance via production of reactive oxygen species was considered. JB induced significant levels of ROS in treated cancer cells including vincristine-resistant cells, possibly contributing to their growth inhibitory and apoptotic destiny. Vincristine was unable to induce reactive oxygen production in vincristine-resistant cells. JB acetate demonstrated enhanced chemical stability compared to JB which could be the reason behind the greater potency of jerantinine B acetate compared to JB. Improvement in the targeting JB acetate to HER2-overexpressing breast cancer cells was attempted following conjugation of JB acetate to the HER2 affibody; potency was enhanced 2.25-fold when cells were exposed to the conjugate compared with JB acetate alone. The jerantinine alkaloid family represent a promising class of novel alkaloids which may produce putative clinical candidate molecules with broad-spectrum antitumour activity.